2020
DOI: 10.1186/s40662-020-0175-9
|View full text |Cite
|
Sign up to set email alerts
|

Evening exercise is associated with lower odds of visual field progression in Chinese patients with primary open angle glaucoma

Abstract: Background: Exercise is widely known to lower intraocular pressure and increase ocular blood flow, which may be beneficial for glaucoma management. However, there are few studies that have reported on the relationship between exercise and glaucoma progression. The aim of our study was to investigate the exercise habits of those with primary open angle glaucoma (POAG) and its association with the progression of visual field (VF) loss. Methods: Daily physical activity (PA) was monitored by an accelerometer (Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This crosssectional study also could not preclude the possibility that some movement behaviors such as MVPA and sleep might affect the risk of glaucoma onset and progression, which had been discussed in numerous studies. 18,42,43 Another major limitation was that measurements of vision function such as VF and contrast sensitivity were unavailable in the current study. Compared with previous studies, 18,19 these might bias the current results and restrict interpretation and exploration of underlying mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This crosssectional study also could not preclude the possibility that some movement behaviors such as MVPA and sleep might affect the risk of glaucoma onset and progression, which had been discussed in numerous studies. 18,42,43 Another major limitation was that measurements of vision function such as VF and contrast sensitivity were unavailable in the current study. Compared with previous studies, 18,19 these might bias the current results and restrict interpretation and exploration of underlying mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…18,42,43 Another major limitation was that measurements of vision function such as VF and contrast sensitivity were unavailable in the current study. Compared with previous studies, 18,19 these might bias the current results and restrict interpretation and exploration of underlying mechanisms. 44 In addition, most covariates were derived from questionnaires and interviews, which were subject to recall bias.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many experimental studies have reported benefits of PA and exercise on cognitive function in older adults [54][55][56]. Regarding glaucoma, it has been suggested that low to moderate intensity aerobic exercise may reduce IOP and improve neural activity in the visual pathway [25][26][27]. However, heavy strength exercise could have a negative impact on IOP control [57], thus, highlighting the need for the careful design and implementation of PA programs for glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that PA can enhance cognitive function, most studies [23,24] have been in healthy older adults; thus, the applicability of these findings to older adults with glaucoma is debatable. It is known that some kind of PA can reduce the development and progression of glaucoma by lowering intraocular pressure (IOP) and increasing ocular blood flow [25][26][27][28]. However, little is known about how PA, particularly for patients with moderate and advanced stage glaucoma, affects visuomotor performance.…”
Section: Introductionmentioning
confidence: 99%